The Relationship between Business Intelligence and Corporate Social Responsibility: An Applied Study on Private Sector Companies in Saudi Arabia - Al-Dabian, Fawzia Abdullah (The Arab Journal of Administration, 2025)
The study aimed to explore the reality of business intelligence in private sector companies in Saudi Arabia, understand the current practices of corporate social responsibility (CSR) in these companies, and determine the nature of the relationship between business intelligence and CSR within the private sector in Saudi Arabia. The study followed a descriptive methodology and included a sample of 350 employees from private sector companies in Saudi Arabia. A questionnaire was used as the primary tool to collect responses from the study sample. The study reached the following results: The mean value for the overall score of the first variable, “the state of business intelligence in private sector companies,” was 4.155 out of 5, with a relative weight of 83.09%, indicating a high level of agreement. The dimensions of business intelligence were ranked in ascending order as follows: data collection, data warehousing, data analysis, data mining, and data presentation. The mean value for the overall score of the second variable, “the state of corporate social responsibility practices in private sector companies,” was 4.114 out of 5, with a relative weight of 82.29%, also indicating a high level of agreement. The dimensions of CSR were ranked in ascending order as follows: legal responsibility, ethical responsibility, and economic responsibility. There is a statistically significant relationship at the significance level of (α≤0.05) between the state of business intelligence in private sector companies and its dimensions and the state of CSR practices and its dimensions among employees in private sector companies in Saudi Arabia. In light of these results, the study recommended increasing investment in business intelligence technologies and tools, such as data collection, analysis, and data mining, to ensure the improvement of operational efficiency and informed decision-making.